Histological Assessment of the Anti-Inflammatory Effectiveness of Peperomia pellucida Extract Administered to the Gingival Sulcus in Rats Induced with Periodontitis - Nasution, Dewi Lidya Ichwana; Tjahajawati, Sri; Indriyanti, Ratna; Amaliya, Amaliya; Irsyad, Widya; Sabirin, Indah Puti (European Journal of Dentistry, 2025)
This study aims to assess the impact of Peperomia pellucida extract on periodontitis in rats, using the Papillary Bleeding Index (PBI), gingival index (GI), and histological evaluation of key inflammatory cells such as osteoclasts, osteoblasts, polymorphonuclear neutrophils (PMNs), macrophages, and fibroblasts to explore its potential in reducing inflammation and preserving periodontal tissue.The extract was prepared using the reflux method with 96% ethanol as a solvent, followed by phytochemical screening and antibacterial testing via the disk diffusion method. This in vivo study utilized a posttest control group experiment with 24 Wistar rats, divided into four groups: nonperiodontitis, no-treatment, chlorhexidine-treated (CHX), and extract-treated groups, with the latter three groups induced with periodontitis. Induction was performed using a 0.3-mm ligature wire and plaque from periodontitis patients, along with nicotine administration (0.001 mg/L) for 7 days. The extract group received a topical application of 2.5 µL of P. pellucida leaf extract, while the CHX group was administered 0.05 mL of CHX daily for 1 week. Observations of GI and PBI were made on days 0, 3, 5, and 7. Histological changes were assessed on day 7 by evaluating the cell counts of osteoclasts, osteoblasts, fibroblasts, macrophages, and PMNs.Data were analyzed using one-way analysis of variance and Kruskal–Wallis with Mann–Whitney post hoc tests for pairwise comparisons.Phytochemical analysis confirmed the presence of alkaloids, polyphenols, tannins, flavonoids, quinones, monoterpenoids, and sesquiterpenoids in P. pellucida extract. The extract demonstrated antibacterial activity against Porphyromonas gingivalis, a key pathogen in periodontitis. Clinical and histological assessments showed significant improvements in the extract-treated group, with outcomes comparable to the CHX-treated group after 7 days.Based on these findings, P. pellucida (L.) Kunth extract contains phytochemicals and exhibits antibacterial and anti-inflammatory properties, as demonstrated by clinical and histological parameters in rats induced with periodontitis.
Keywords: Peperomia pellucida; periodontitis; anti-inflammatory; antimicrobial activity; Wistar rats